2011
DOI: 10.1111/j.1574-6941.2011.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with a mineral weathering profile at a sulphidic mine tailings dump in arid Western Australia

Abstract: We investigated bacterial community assemblages and functions down a hill slope contaminated by tailings from a volcanogenic massive sulphide mine in arid Western Australia. Weathering of waste rock, high in S and Fe, had resulted in a varying elemental dispersal down a face of the tailings hill. Bacterial community assemblage, characterised by PCR-DGGE fingerprinting, was significantly associated with electrical conductivity (E.C.) (ρ = 0.664; P < 0.01). Analysis of mobile salts showed that E.C. values were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…This agreed with the findings of Siggins et al (22), who suggested, based on the survey of bacteria commu- Conductivity is an index measured by the number of ions relative to salinity, and it was strongly and significantly linked to bacterial community variance in CCA. Previous studies have found salinity to be an important factor regulating bacterial composition and diversity across a variety of habitats (12,13,16,26).…”
Section: Resultsmentioning
confidence: 99%
“…This agreed with the findings of Siggins et al (22), who suggested, based on the survey of bacteria commu- Conductivity is an index measured by the number of ions relative to salinity, and it was strongly and significantly linked to bacterial community variance in CCA. Previous studies have found salinity to be an important factor regulating bacterial composition and diversity across a variety of habitats (12,13,16,26).…”
Section: Resultsmentioning
confidence: 99%
“…The results from this study showed that mobile phase elements, such as sulfur, zinc, chloride and aluminum, were the dominant drivers of bacterial community structures at this site. Using PhyloChip the authors were able to identify a greater level of species richness than had been reported at similar sites in the past [86,87]. In another study, 187 soil samples were collected from four naturally metallomorphic sites spanning three climatic zones across Australia to assess the links between soil microbial communities and geogenic factors, namely the underlying geology, the position in the landscape, i.e., regolith landform, and the presence of gold mineralization [54].…”
Section: Bioindicatorsmentioning
confidence: 99%
“…However, few studies exist that have assessed microbial communities in geogenic metallomorphic environments with low to moderate metal contents, such as soils overlying buried mineralization [55,85]. Wakelin et al [86,87] integrated several techniques to gain a better understanding of the composition and function of bacterial communities from a sulfidic mine tailing dump located 600 km northeast of Perth, Western Australia. Differences in bacterial communities were first assessed with DGGE and then members of the community were further identified using the PhyloChip.…”
Section: Bioindicatorsmentioning
confidence: 99%
“…Using culture-based approaches, correlations between abundances of Bacillus cereus spores and the presence of Au and its pathfinder elements (i.e., As, Ag, Bi, Cu, Mo, Se, and Te) in soils overlying Au deposits in Belgium, the United States, and Australia have been observed (18)(19)(20). In Western Australian soils overlying Cu-Pb-Zn deposits, the solubilization, transport, and deposition of metals is mediated by resident plant and microbial communities (21,22). Subsequently, elevated concentrations of mobile metals in the soils are related to changes in the microbial community composition.…”
mentioning
confidence: 99%
“…Subsequently, elevated concentrations of mobile metals in the soils are related to changes in the microbial community composition. In particular, highly mobile elements, e.g., S, Zn, Cl, and Al, were implicated as drivers of bacterial community structures across these sites (21,22). A study of 187 soils collected at four naturally auriferous (i.e., Au-containing) areas in remote Australia has shown that microbial communities and functional potentials differ significantly with landform, soil depth, lithology, and Au deposits (23).…”
mentioning
confidence: 99%